1982
DOI: 10.1080/0380127820080107
|View full text |Cite
|
Sign up to set email alerts
|

Sex Stereotyping of the Elderly by Children

Abstract: The purpose of this study was to investigate whether elementary pupils stereotype older people and, more specifically, whether they stereotype them by sex. Photographs of a young woman and man and an old woman and man were shown to the subjects. Subjects were then asked to select the adjective from each of five pairs of adjectives which best described the person, such as happy or sad. Then subjects were asked six questions designed to assess their willingness to associate socially with the persons depicted in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1986
1986
2002
2002

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…However, some evidence suggests that both boys and girls respond more positively to an old woman as stimulus than to an old man (Fillmer, 1982). Further research is needed to address the question of psychosocial developmental factors and gender differences influencing attitudes and attitude change.…”
Section: Gender Differencesmentioning
confidence: 95%
See 1 more Smart Citation
“…However, some evidence suggests that both boys and girls respond more positively to an old woman as stimulus than to an old man (Fillmer, 1982). Further research is needed to address the question of psychosocial developmental factors and gender differences influencing attitudes and attitude change.…”
Section: Gender Differencesmentioning
confidence: 95%
“…However, several studies on children's attitudes suggest that girls generally hold more positive attitudes than boys (Fillmer, 1982;Olejnik & LaRue, 1981;Thomas & Yamamoto, 1975).…”
mentioning
confidence: 95%
“…One methodological issue that has been raised in previous research is that, despite the fact that the majority of the older population are women and that grandmothers may be the only older person children know (Baggett, 1981), certain measures have used only men as stimulus targets. It has been reported that children prefer female stimulus persons to males (Fillmer, 1982;Mitchell et al, 1985;Rosenwasser, McBride, Brantley, & Ginsburg, 1983), and that they remember more positive information about older individual women than men (Davidson et al, 1995). Based on these findings, there appears to be compelling reasons to suggest that the use of women-only stimulus persons should moderate potentially negative attitudinal responses that are directly attributable to gender variables.…”
Section: Materials and Proceduresmentioning
confidence: 99%
“…Several scholars (Fillmer, 1982 ;Marks, Newman, & Onewola, 1983) noted that although children wished to associate with older people, a majority of them selected negative adjectives (weird, scary, lonely, sad, etc.) for the older persons when asked to react to the pictures of young and old.…”
Section: Age or Aging P Er C Ep Tions Of C H Ild R Enmentioning
confidence: 99%
“…Baum, Newman, and Shore (1982) advocated the mutual learning of young and old. Fillmer (1982) found that girls were more willing to associate with older people than boys. Although children made more negative attributions for the photographs of older adults than the younger adults, it was done so for older men more so than the older women.…”
mentioning
confidence: 95%